Designing Interactive Mobile Learning Applications for Visually Impaired Children: A User Experience Evaluation Based on Affective Design Principles Using Hypothetical Datasets and Heatmap Analysis - Nur Abdul Salam, Sobihatun; Abdul Mutalib, Nur Amirah; Aziz, Nurulnadwan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study explores the development and user experience testing of an interactive mobile learning application designed for children with visual impairments integrated with affective design principles. Despite the availability of various assistive technology (AT) solutions, existing mobile applications often fail to address the specific needs of visually impaired children, particularly regarding emotional engagement and usability. Affective design principles are essential in developing functional, emotionally resonant, and engaging products for users. Therefore, this study aims (i) to develop an interactive mobile learning application tailored for visually impaired children based on affective design principles and (ii) to validate the application through comprehensive user experience testing by utilizing a hypothetical dataset and heatmap overlay. Employing iterative triangulation methodology (ITM), the study demonstrates that integrating affective design principles significantly enhances the usability and engagement of mobile learning applications for visually impaired children. The findings highlight the critical role of affective design in promoting equitable and effective learning experiences for this demographic, contributing both theoretically and practically to the field of assistive technology.